German political scene (Economic and Political Thought, 2019)
The political scene of the Federal Republic of Germany was traditionallyrecognised as extraordinarily stable. However, in the second decade of the21st century the pace of changes in it has clearly quickened and they arereshaping it in the long term. The changes are conditioned by internal policyas well as global trends. In the author’s opinion, the change in the Germanpolitical scene does not take place rapidly but one can see the weakening ofthe left wing, the change of the party playing the role of a pivotal one, andprobably the movement of Christian democracy towards the right wing underthe pressure of radical tendencies. The growing difference between the socalledold and new federal states constitutes the biggest threat because thelatter prove to be much more vulnerable to the influence of radically rightmovements.
Keywords: Germany, political parties, Bundestag, AfD, CDU, CSU, SPD, The Greens, Merkel, Bavaria